Method of Selection of Feasibility Criteria Recipients of Msme Cash Direct Assistance With Topsis Method - Alawiah, Enok Tuti; Apriyanto, A; Siregar, Martua Hami (IJISTECH (International Journal of Information System and Technology), 2022)
Micro, Small and Medium Enterprises are one of the sectors most affected by the pandemic. This is indicated by a decrease in business and service production, a decrease in labor and a reduced income turnover. The affected Micro, Small and Medium Enterprises are dominated by the fields of trade, services, creative industries and tourism. The government seeks to encourage economic recovery by providing BLT assistance funds for Micro, Small and Medium Enterprises as an economic stimulus so that Micro, Small and Medium Enterprises can revive. In order for the grants to be right on target, special research using the TOPSIS method is needed. TOPSIS is used to find the preference value that is closest to the optimal final result by calculating and testing alternative criteria. The results of research conducted in the Districts of Dramaga, Tamansari Ciomas and Tenjolaya show that the provision of BLT funds for Micro, Small and Medium Enterprises should be prioritized for MSME actors who have never received Micro Business Aid (BPUM) funds